Fostering the post-development debate: the Latin American concept of tecnologia social - Pozzebon, Marlei; Fontenelle, Isleide Arruda (Third World Quarterly, 2018)
This essay revisits the historical development of a concept – tecnologia social – as one avenue for discussing alternatives to post-development, arguing that the Western-based historical path of technology development is one of the main sources of growing human impoverishment, social inequalities and economic dependency. The concept of tecnologia social points towards political processes that create opportunities to redefine the arrangements among social groups, artefacts and methods used in everyday life, particularly for production and consumption. Because the post-development debate has been criticised for formulating a sound and strong critique to mainstream development but failing to propose concrete empirical alternatives, we seek to foster the debate through the Latin American concept of tecnologia social.
Keywords: Amérique latine; Libre accès; Social technology; Technologie sociale

Fostering the post-development debate: the Latin American concept of tecnologia social - Pozzebon, Marlei; Fontenelle, Isleide Arruda (Third World Quarterly, 2018)
This essay revisits the historical development of a concept – tecnologia social – as one avenue for discussing alternatives to post-development, arguing that the Western-based historical path of technology development is one of the main sources of growing human impoverishment, social inequalities and economic dependency. The concept of tecnologia social points towards political processes that create opportunities to redefine the arrangements among social groups, artefacts and methods used in everyday life, particularly for production and consumption. Because the post-development debate has been criticised for formulating a sound and strong critique to mainstream development but failing to propose concrete empirical alternatives, we seek to foster the debate through the Latin American concept of tecnologia social.
Keywords: Amérique latine; Libre accès; Social technology; Technologie sociale

Fostering the post-development debate: the Latin American concept of tecnologia social - Pozzebon, Marlei; Fontenelle, Isleide Arruda (Third World Quarterly, 2018)
This essay revisits the historical development of a concept – tecnologia social – as one avenue for discussing alternatives to post-development, arguing that the Western-based historical path of technology development is one of the main sources of growing human impoverishment, social inequalities and economic dependency. The concept of tecnologia social points towards political processes that create opportunities to redefine the arrangements among social groups, artefacts and methods used in everyday life, particularly for production and consumption. Because the post-development debate has been criticised for formulating a sound and strong critique to mainstream development but failing to propose concrete empirical alternatives, we seek to foster the debate through the Latin American concept of tecnologia social.
Keywords: Amérique latine; Appropriation technologique; Social technology; Technologie sociale

Nourishing the Social Innovation Debate with the “Social Technology” South American Research Tradition - Pozzebon, Marlei; Tello-Rozas, Sonia; Heck, Isabel (Voluntas, 2021)
Inspired by the South American research tradition known as “social technology,” this article proposes an operational framework to advance the understanding of mechanisms that help to promote social transformation. To illustrate its theorizing potential, we apply the framework to a nonprofit organization–Parole d’excluEs–that was created in Montreal (Canada) in 2006 and that has been promoting citizen mobilization and commitment to social change (parole-dexclues.ca). To that end, we offer a theoretical paper with an empirical illustration as a first step in a reflection on employing a global South theoretical lens–drawing on the concept of social technology–to make sense of a global North social innovation experience and to advance existing knowledge on the mechanisms of social transformation. The results contribute to social innovation research and practice, particularly at the interface between the management and nonprofit literatures.
Keywords: Amérique centrale/sud; Amérique latine; Canada; Changement social; Innovation sociale; Montréal; Nord / Sud; Recherche; Technologie sociale; Transformations

Nourishing the Social Innovation Debate with the “Social Technology” South American Research Tradition - Marlei, Pozzebon; Tello-Rozas, Sonia; Heck, Isabel (Voluntas, 2021)
Inspired by the South American research tradition known as “social technology,” this article proposes an operational framework to advance the understanding of mechanisms that help to promote social transformation. To illustrate its theorizing potential, we apply the framework to a nonprofit organization–Parole d’excluEs–that was created in Montreal (Canada) in 2006 and that has been promoting citizen mobilization and commitment to social change (parole-dexclues.ca). To that end, we offer a theoretical paper with an empirical illustration as a first step in a reflection on employing a global South theoretical lens–drawing on the concept of social technology–to make sense of a global North social innovation experience and to advance existing knowledge on the mechanisms of social transformation. The results contribute to social innovation research and practice, particularly at the interface between the management and nonprofit literatures.
Keywords: Amérique latine; Canada; Changement social; Innovation sociale; Montréal; Recherche; Technologie sociale; Transformations

Nourishing the Social Innovation Debate with the “Social Technology” South American Research Tradition - Pozzebon, Marlei; Tello-Rozas, Sonia; Heck, Isabel (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2021)
Inspired by the South American research tradition known as “social technology,” this article proposes an operational framework to advance the understanding of mechanisms that help to promote social transformation. To illustrate its theorizing potential, we apply the framework to a nonprofit organization–Parole d’excluEs–that was created in Montreal (Canada) in 2006 and that has been promoting citizen mobilization and commitment to social change (parole-dexclues.ca). To that end, we offer a theoretical paper with an empirical illustration as a first step in a reflection on employing a global South theoretical lens–drawing on the concept of social technology–to make sense of a global North social innovation experience and to advance existing knowledge on the mechanisms of social transformation. The results contribute to social innovation research and practice, particularly at the interface between the management and nonprofit literatures.

SOCIAL INNOVATION IN THE CULTURAL SECTOR: THE CASE OF PJE/PRODIGIUM - Saldanha, Fabio Prado; Delgado, Natalia Aguilar; Pozzebon, Marlei (Revista Brasileira de Casos de Ensino em Administração, 2021)
This case examines the major challenges faced by Productions Jeun’Est (PJE) and Prodigium, a social enterprise working in the cultural sector. The profits generated by Prodigium’s activities in the entertainment field are invested in the PJE training program that aims to increase the social inclusion of vulnerable youth by training them to be technicians in the cultural market. By studying this case, students are expected to understand the elements of a social business model, to analyze the role of the different elements forming a social innovation and to evaluate the challenges of planning its transfer to another context.

‘Tecnologia social’ and social change: the case of Agência de Redes in Rio de Janeiro - Saldanha, Fabio Prado; Aguilar-Delgado, Natalia; Pozzebon, Marlei (Revista Brasileira de Casos de Ensino em Administração, 2019)
The case provides an opportunity to understand how tecnologia social – a South American concept that might be seen as an equivalent to social innovation – can help promote social change. To illustrate the potential of social technologies, the case of Agência de Redes is presented. The case is intended for use at both the undergraduate and graduate levels. Its purpose is to promote the discussion of the South American concept of tecnologia social, as well as to analyse of one particular tecnologia social using a conceptual model to understand the mechanisms that might promote social change.